Dissemination of responsible information in sport through websites - Pache Durán, M.; Nevado Gil, T.; Carvalho, L. C.; Paiva, I. (Transinformação, 2022)
In recent years, there is a growing consensus on the importance of Corporate Social Responsibility for organisations with the aim of achieving sustainable development. This study aims to analyse the dissemination of information on Corporate Social Responsibility through the websites of Portuguese Liga NOS clubs in the 2017/2018 sport season. The study is descriptive in nature and is based on a qualitative methodology using the content analysis technique. The results show that the degree of information disclosed is low, as revealed by the total disclosure index (26.63%), and that the most disclosed information is social, followed by economic information. However, very little information is disclosed on employee recruitment and environment. _____ En los últimos años, está siendo consensuada cada vez más la importancia en lo que respecta a la Responsabilidad Social Corporativa para las organizaciones con el objetivo de alcanzar un desarrollo sostenible. El presente estudio tiene como objetivo analizar la divulgación de información sobre Responsabilidad Social Corporativa a través de las páginas web de los clubes portugueses de la Liga NOS en la temporada deportiva 2017/2018. El estudio es de carácter descriptivo y se basa en una metodología de tipo cualitativo utilizando la técnica de análisis de contenido. Los resultados muestran que el grado de información divulgado es bajo, como lo revela el índice de divulgación total (26,63%), y que la información más divulgada es la social, seguida de la información económica. Sin embargo, la información propagada sobre la contratación de los colaboradores y la medioambiental es muy escasa.